Efficient Method to Synthesize Benzhydrazides by In Situ Oxidation/Coupling of Benzylic Alcohols with Azodicarboxylates - Azizi, Kobra; Heydari, Akbar (Synlett, 2018)
An efficient synthesis of benzhydrazides has been achieved through the direct acylation of azodicarboxylates with benzylic alcohols in moderate to high yields. The method represents the first practical approach to amides containing a hydrazine structural unit from benzylic alcohols.
Keywords: benzhydrazides; hydroacylation; azodicarboxylates; C–N bond formation